The Idea of Establishing the International Court for Constitutional law: A New Guarantee for Constitutional Governance - حوسێن حه‌سه‌ن; ويسي عثمان (Academic Journal of Nawroz University, 2023)
Humanity’s efforts to build a society in which prosperity and happiness prevail and in which people live in peace and security are due to a civilizational background that has historical roots. By referring to the "Greek" political thought in general and the political thought of (Plato and Aristotle) ​​in particular and extending to modern philosophy, it is clear that the issue of the virtuous city or the ideal political system is one of the most important topics that attract significant attention among thinkers and specialists in philosophical field and political science. Constitutionalism and constitutional governance as a modern movement in constitutional thought is an important step towards building a system of government that adopts constitutional rules and principles. Given this importance, this form of government is considered one of the greatest achievements of modern civilization through which a measure of freedom, prosperity and coexistence among human beings has been achieved. However, it is noted that despite the existence of written constitutions in some countries, the legitimacy of the ruling regimes is still a matter of serious question. Where the issue of democracy, the protection of human rights and dignity, the sovereignty of the people, periodic elections, the peaceful transfer of power, respect for the rights of minorities, the right to self-determination, and resistance to tyranny are exposed to multiple problems and challenges. From this angle and in order to establish a constitutional state and a real constitutional governance, jurists of contemporary constitutional law are studying the idea of ​​an international constitutional court. These jurists also seek to answer several questions and examine that necessity and search for a group of main issues that are represented in discussing the role that this court can play in implementing the constitution and protecting individuals and societies from unjust rule and the opportunity to live in accordance with international values, away from the means of violence and chaos, contribute to progress and development. Accordingly, this study is considered an in-depth scientific attempt to study and analyze the idea of ​​establishing the International Constitutional Court, presenting the substantive and procedural terms of reference for this court and indicating its future challenges and prospects.